Financial Pattern of Small Business Enterprises and Traders: Exploring the Financing Patterns and Challenges of Small Business Enterprises in India (Journal of Advances and Scholarly Researches in Allied Education, 2019)
There is no uncertainty that entrance to finance is of pivotal significance for the progressing and supportable development and gainfulness of small and medium enterprises sector (SMEs) through its job in encouraging the production of new businesses and sustaining the advancement procedure just as advancing the development and improvement of existing businesses, which thus, help national financial development. This investigation centers around the organization-wise financing pattern of small and medium scale industries (SMEs). It endeavors to survey the connection between forms of business and sources of capital financing among SMEs in India, one of the developing markets in Asia. Utilizing factor analysis technique, the investigation finds that the capital needs of the business visionaries are met with the bank advances, cash loan specialists, creditor liability and companions and relatives. These sources of capital are not effectively open by various business organizations to satisfy their capital necessity. What's more, analysis of optional information uncovers that modern credit conveys certain banking limitations, which should be distinguished to help in advancing the SME sector by giving a few recommendations required to the new financial policy routine.